Please help me answer this question
![Please help me answer this question class=](https://us-static.z-dn.net/files/df8/15ff78bca9fea8c76515a39fd76c0473.jpg)
By direct substitution and simplification, the trigonometric function z = cos (2 · x + 3 · y) represents a solution of the partial differential equation [tex]\frac{\partial^{2} t}{\partial x^{2}} - \frac{\partial^{2} t}{\partial y^{2}} = 5\cdot z[/tex].
Differential equations are expressions that involve derivatives. In this question we must prove that a given expression is a solution of a differential equation, that is, substituting the variables and see if the equivalence is conserved.
If we know that [tex]z = \cos (2\cdot x + 3\cdot y)[/tex] and [tex]\frac{\partial^{2} t}{\partial x^{2}} - \frac{\partial^{2} t}{\partial y^{2}} = 5\cdot z[/tex], then we conclude that:
[tex]\frac{\partial t}{\partial x} = -2\cdot \sin (2\cdot x + 3\cdot y)[/tex]
[tex]\frac{\partial^{2} t}{\partial x^{2}} = - 4 \cdot \cos (2\cdot x + 3\cdot y)[/tex]
[tex]\frac{\partial t}{\partial y} = - 3 \cdot \sin (2\cdot x + 3\cdot y)[/tex]
[tex]\frac{\partial^{2} t}{\partial y^{2}} = - 9 \cdot \cos (2\cdot x + 3\cdot y)[/tex]
[tex]- 4\cdot \cos (2\cdot x + 3\cdot y) + 9\cdot \cos (2\cdot x + 3\cdot y) = 5 \cdot \cos (2\cdot x + 3\cdot y) = 5\cdot z[/tex]
By direct substitution and simplification, the trigonometric function z = cos (2 · x + 3 · y) represents a solution of the partial differential equation [tex]\frac{\partial^{2} t}{\partial x^{2}} - \frac{\partial^{2} t}{\partial y^{2}} = 5\cdot z[/tex].
To learn more on differential equations: https://brainly.com/question/14620493
#SPJ1